Impact of Fire on Natural Regeneration in Peat - Bambang Hero Saharjo; Ati Dwi Nurhayati (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2007)
Fire is one of the most effective tools in disappearing vegetation community, where it was depend on the characteristics of burning itself and also the performance of the site being burnt. Previous research in mineral soils showed that repeated burning occurred at the same place trend to clean the vegetation which finally leads to have the land with lower number and quality of species left, while in peat land it was not fully understood. The research objective is to understand the vegetation dynamics following peat fires in the fibric peat type at the land preparation area using fire belong to the local community located in the Pelalawan district, Riau province, Indonesia during the dry season in the year 2001. Before slashing and drying, /0 tree species and 4 species of under storey vegetationfound. The site was dominated by Uncaria glabrata at seedling stage, Garcinia rostrata at sapling stage, Shorea macrophylla at pole stage and Pandanus immersus at understorey. After slashing and followed by 4 weeks drying then continued by burning with high flame temperature range from 8750(; to 900°C, it had been found that 3-months follOWing burning the site was dominated by Garcinia-rostrata at seedling stage and Cyperus halpan at understorey, while 6-months following burning the site was dominated by Eugenia jambos at seedling stage and Cyperus hal pan at understorey. Three months following burning species left to be only 4 species with 115 individuaVha (3 species from original and 1 new species emerge), and at 6 months following burning still 4 species left with 250 individuaVha.Meanwhile in understorey vegetation, 3 months following burning the species increased to be 7 species with 746 individuaVha (3 species left unchanged, I species disappeared and 4 new species emerge) and 6 months following burning the species left still 7 species with 1235 individuaVha. This means thatfire stimulate the increasing number of under storey vegetation.